Deskripsi Pelayanan Konseling dalam Etis Kristiani Bagi Pendidikan Karakter Kristen - Lahingide, Yenni Olivia; Sumiyati, Sumiyati (Sekolah Tinggi Teologi Kanaan Nusantara, 2021)
Counseling is always related to a solution that will be sought to solve every problem, the solution sought is of course based on the truth of God's word, restoring a fragile condition means that the counseling process can restore a fragile and fragile condition that is replaced with toughness, patience and fortitude, change attitudes and behavior. Using descriptive qualitative methods with the aim of the importance of counseling services in Christian ethics, counseling services in Christian ethics for Christian education and character can be concluded that counseling services must be maintained as indicated by the statement item